2019
DOI: 10.21733/ibad.505283
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇nde Duygudurum Düzenleme Ve Öfke

Abstract: Adolescence is a period of development that is critical to social and emotional development. Successful emotion regulation in this period will bring success in social relations. The sense of anger that has the potential to cause problems individually, interpersonally and socially is seen as a frequently observed feeling during adolescence. Therefore, it was aimed to investigate the relationship between anger levels and emotion regulation methods of this age group. For this purpose, two scales, the Adolescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Nitekim ülkemizde sürdürülen bir çalışmada duygu düzenlemenin sosyal kaygının belirleyicisi olduğu da gösterilmiştir (Yılmaz, Yazar ve Tolan, 2021). Yine ülkemizde sürdürülen başka bir çalışmada, ergenlerde duygu düzenlemenin öfke kontrolü üzerinde de etkisinin olduğu bulunmuştur (Duman, Yılmaz, Umunç ve İmre, 2019). Bu bulgular, duygu düzenlemenin ergenler arasındaki davranışsal ve duygusal sorunların merkezi bir bağlantısı olabileceği görüşünü destekler niteliktedir (Silk, Steinberg ve Morris, 2003).…”
Section: Uluslararası Anadolu Sosyal Bilimler Dergisiunclassified
“…Nitekim ülkemizde sürdürülen bir çalışmada duygu düzenlemenin sosyal kaygının belirleyicisi olduğu da gösterilmiştir (Yılmaz, Yazar ve Tolan, 2021). Yine ülkemizde sürdürülen başka bir çalışmada, ergenlerde duygu düzenlemenin öfke kontrolü üzerinde de etkisinin olduğu bulunmuştur (Duman, Yılmaz, Umunç ve İmre, 2019). Bu bulgular, duygu düzenlemenin ergenler arasındaki davranışsal ve duygusal sorunların merkezi bir bağlantısı olabileceği görüşünü destekler niteliktedir (Silk, Steinberg ve Morris, 2003).…”
Section: Uluslararası Anadolu Sosyal Bilimler Dergisiunclassified
“…The cognitive behavioral program, on the other hand, was more effective in younger adolescents. It was observed that there was a decrease in the anger inside and anger outside levels and improvements in the anger management levels of students who benefited from the cognitive behavioral therapy-based program conducted by Duman et al (2019). Özkamalı and Buğa (2010) determined that the anger management education program reduced students' trait anger levels.…”
Section: Introductionmentioning
confidence: 99%
“…Anger management skills are critical in adolescence, during which emotional fluctuations are often observed (Duman, Yılmaz, Umunç, & İmre, 2019; Özmen, Özmen, Çetinkaya, & Akil, 2016). In fact, the acquisition of emotion regulation skills in adolescents is accepted as a protective factor against later adverse experiences (Mazza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%